Restorative justice from theory to practice - Miller, Holly Ventura (Bingley : Emerald JAI, 2008)
"Sociology of Crime, Law and Deviance" is an annual series of volumes that publishes scholarly work in criminology and criminal justice studies, sociology of law, and the sociology of deviance. Each volume revolves around one central theme in any of these areas, broadly defined. Showcasing a diversity of methodological approaches, work published in the series includes theoretical contributions, critical reviews of literature, empirical research, and methodological innovations.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Restorative justice; Criminal justice, Administration of; Causes & prevention of crime; Social theory; Social Science -- Criminology; Electronic books